National ICT-Driven Development Policy: Comparing Approaches in India and China - Nirupam Bajpai; John Biberman; Yingxin Ye (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2018)
The two largest countries in the world have experienced immense economic transitions over the past three decades. In both countries, market-driven reforms have transformed economies under heavy state regulation into engines of economic growth lifting hundreds of millions out of poverty. Since the turn of the 21st century, Information and Communications Technology (ICT) has played an increasingly greater role in the growth and development of both countries. In China, ICT has facilitated greater integration into global supply chains for the booming manufacturing sector, while in India, it has enabled a rapidly growing services sector to drive the economy in a way not previously seen in developing countries. In the near future, ICT has the capacity not just to accelerate growth for both countries, but also to support more equitable and sustainable development in rural and urban areas alike. This paper, part of a larger series on ICT-driven development, provides a brief overview of growth trends in India and China over the past few decades, with a focus on the role of ICT in this growth. It then examines existing national strategy regarding the implementation of ICT and AI for the purposes of sustainable development, before exploring key issues and challenges regarding the continued promotion of ICT-led growth and development. Future papers will explore national and subnational ICT platforms and policies in the health, education, infrastructure, agriculture, and urban development sectors for both countries.
Keywords: 330